Corporate liquidity as a predictor variable of firm earnings in the Nigerian agricultural sector - Ofulue, Igbodo; Okike, Juliet Ogbonneya; Nworie, Gilbert Ogechukwu; Nworie, Fidelia Nkechinyere (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study examines the effect of corporate liquidity on the earnings of listed agricultural firms in Nigeria. The proxies of corporate liquidity are net working capital and cash level. Method: This study adopted an ex-post facto research strategy. The population consisted of five listed agricultural firms in Nigeria, and census sampling was applied in the study. Secondary data were gleaned from the annual reports of firms from 2014 to 2023. A fixed-effects estimation model was used to test the hypotheses. Results: Net working capital has a significant positive effect on the earnings of listed agricultural firms in Nigeria, and cash level has a significant positive effect on the earnings of listed agricultural firms in Nigeria. Conclusions: Firms that can optimize their liquidity positions are more agile in taking advantage of business opportunities, such as acquiring raw materials at favorable prices or capitalizing on market demand surges. Limitations: A key limitation of this study is its relatively small sample size, as it exclusively examines listed agricultural firms in Nigeria. Consequently, these findings may not be fully generalizable to unlisted agricultural firms.   Contribution: This study contributes to the literature by filling a critical gap by focusing on sector-specific profitability metrics, as it offers a new perspective on the liquidity-performance relationship in Nigerian agricultural firms. Implications: Financial managers of listed agricultural firms in Nigeria need to adopt proactive working capital management strategies by ensuring efficient accounts receivable collection and maintaining a balanced accounts payable structure.